2020
DOI: 10.1186/s41100-019-0252-5
|View full text |Cite
|
Sign up to set email alerts
|

A new assessment scale for post-dialysis fatigue in hemodialysis patients

Abstract: Development of the PDF scale Create item pool To create items for the PDF scale, a post-dialysis interview was conducted in five maintenance hemodialysis patients with different severities. The item pool was collected using three anonymous questions. The first asked, "Are there any symptoms that develop after dialysis and then recover?" The second asked, "What exactly is that symptom?" The third question, which was asked while showing the patient a health card (basic life study, symptom list), was, "Are there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…Both correlation coefficients were above the 0.30 required to show criterion validity. Kodama et al 9 who developed the PDF Scale, similarly used the VAS score and fatigue scale to evaluate criterion validity and found correlation coefficients of 0.670 and 0.732, respectively. They also found a significant relationship between the PDF Scale scores and both the VAS and Fatigue Scale scores 9 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Both correlation coefficients were above the 0.30 required to show criterion validity. Kodama et al 9 who developed the PDF Scale, similarly used the VAS score and fatigue scale to evaluate criterion validity and found correlation coefficients of 0.670 and 0.732, respectively. They also found a significant relationship between the PDF Scale scores and both the VAS and Fatigue Scale scores 9 …”
Section: Discussionmentioning
confidence: 99%
“…One strength of this study is adding a measurement tool specific to PDF for the first time in our country. Another strength is the confirmation of the consistency over time with the test‐retest method, something that was not tested by Kodama et al 9 It was, therefore, possible to measure the consistency over time of the PDF Scale and show that it is a consistent measurement device. The final strength is the fact that the study was conducted at two dialysis centres in two different cities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In situational factors, it was found that the length of time in undergoing hemodialysis with an average of above 6 years, has comorbid diseases (8,18,26) such as cardiovascular and diabetes mellitus (26), the frequency of hemodialysis of 3 times a week (22,24), has disease complications (21,24) have a higher rate of fatigue, but the relationship with fatigue is not clear enough. There are studies that found there is no relationship between comorbid diseases (p-value 0.938) (8), length of time in undergoing hemodialysis (r = −0.154, p-value 0.086), diabetes mellitus (r = 0.128, p-value 0.157), the frequency of dialysis (F = 2.156, p-value 0.119) (22), and cardiovascular disease (r = 0.151, p-value 0.092) (26) with fatigue in hemodialysis Factors Associated with Fatigue in Chronic.... patients. However, other studies found that there is a relationship between cardiovascular disease (standard error of 2.15, p-value 0.01) (19), comorbid diseases (pvalue 0.001) (17), the frequency of dialysis (mean 260.00, p-value <0.001) (24) with fatigue.…”
Section: Situational Factorsmentioning
confidence: 99%